(untitled) (Journal of Parents and Teachers, 2014)
The importance attached to the balanced development of intelligence and the need to enhance effective family-center relationship leads us to revise and improve the content, strategies and intervention techniques. The article summarizes the lines of a proposal that the author is coordinating centers and 350 representing the integrated meetings, interviews, job materials and workshops.